Why Credit Rating Agencies Exist. (14th April 2015) - Rhee, Robert J.
<x xml:space="preserve">Abstract</x> Although credit rating agencies exist and are important to the capital markets, there remains a question of why they should exist. Two standard theories are that rating agencies correct a problem of information asymmetry and that they de facto regulate investments. These theories do not fully answer the question. This paper suggests an alternative explanation. While rating agencies produce little new information, they sort information available in the credit market. This sorting function is needed due to the large volume of information in the credit market. Sorting facilitates better credit analysis and investment selection, but bond investors or a cooperative of them cannot easily replicate this function. Outside of their information intermediary and regulatory roles, rating agencies serve a useful market purpose even if credit ratings inherently provide little new information. This alternative explanation has policy implications for the regulation of the industry.